Observation of peri-implant bone loss rates in patients visiting dentist—A retrospective evaluation of patients of a faculty hospital for one year - Ilkim Karadag; Halis Kurnaz; Mehmet Murat Akkaya; İrem Karadag; Zeynep Ilayda Konukçu Kurnaz (PeerJ)
Background Many studies have been published on the relationship between different parameters with marginal bone loss around implants. The results of these studies vary, but some variables such as smoking or certain systemic conditions are more likely to predispose or exacerbate the resorption around implants. The aim of this study was to determine the rates of implants with radiographically detected marginal bone loss and to determine whether there is a relationship between the severity of destruction and certain risk factors like location of implant, restoration type, systemic condition, age, sex or smoking habits. Materials and Methods Panoramic radiographs obtained for 1 year were examined. Patients with bone loss around the implant were classified according to the region of implant placement, type of restoration on implants, systemic diseases, and smoking habits. The rate of bone loss around the implants was recorded as the resorption score. Double and multiple comparison tests were applied to observe whether the resorption scores were related to the variables. Results Of 17,352 patients, 1,465 had at least one implant, and 1,116 of these had no bone loss. A total of 181 patients (863 implants) included in the study, there was a weak correlation between age (p = 0.017) and resorption rate. Implants supporting bridge restorations had higher resorption scores. Gender, age, and systemic conditions alone are not effective in increasing peri-implant bone loss (p < 0.05); therefore, placing implants in the mandible (p = 0.020) or using implants to support bridge restorations(p = 0.027) may make implants more vulnerable to resorption.